2020
DOI: 10.3389/fpls.2020.01283
|View full text |Cite
|
Sign up to set email alerts
|

H2S Regulation of Metabolism in Cucumber in Response to Salt-Stress Through Transcriptome and Proteome Analysis

Abstract: In a previous study, we found that H 2 S alleviates salinity stress in cucumber by maintaining the Na + /K + balance and by regulating H 2 S metabolism and the oxidative stress response. However, little is known about the molecular mechanisms behind H 2 S-regulated saltstress tolerance in cucumber. Here, an integrated transcriptomic and proteomic analysis based on RNA-seq and 2-DE was used to investigate the global mechanism underlying H 2 S-regulated salt-stress tolerance. In total, 11,761 differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…DEGs identified in the DND252 variety were primarily enriched in cellular amide metabolic processes, cell, binding, and catalytic activity, whereas DEGs identified in the HN84 variety were primarily enriched in cellular processes, membranes, and binding. A transcriptome analysis of cucumber treated with H 2 S showed that the DEGs were primarily enriched in inherent components of the membrane [31], which is similar to the findings of the present study, suggesting that sulfur affects the cell membranes.…”
Section: Discussionsupporting
confidence: 89%
“…DEGs identified in the DND252 variety were primarily enriched in cellular amide metabolic processes, cell, binding, and catalytic activity, whereas DEGs identified in the HN84 variety were primarily enriched in cellular processes, membranes, and binding. A transcriptome analysis of cucumber treated with H 2 S showed that the DEGs were primarily enriched in inherent components of the membrane [31], which is similar to the findings of the present study, suggesting that sulfur affects the cell membranes.…”
Section: Discussionsupporting
confidence: 89%
“…H 2 S could promote photosynthetic electron transfer, chlorophyll biosynthesis and carbon fixation in Kandelia obovata leaves and cucumber under salt stress (Jiang et al 2020 ; Liu et al 2020d ). In addition, the abundance of other proteins related to the metabolic pathways, such as antioxidation (APX, copper/zinc superoxide dismutase, pancreatic and duodenal homeobox 1), protein synthesis (heat-shock protein (HSP), chaperonin family protein 20 and Cysteine synthase 1), nitrogen metabolism (glutamine synthetase 1 and 2), glycolysis (phosphoglycerate kinase and triosephosphate isomerase), and the AsA-GSH cycle (glutathione S-transferase U25-like), was increased by H 2 S under high salinity (Jiang et al 2020 ; Liu et al 2020d ). However, the mechanism underlying the effect of H 2 S on such huge proteins remains unclear (Guo et al 2018 ; Li et al 2014a , 2020c ).…”
Section: H 2 S Positively Responds To Biotic and Amentioning
confidence: 99%
“…Furthermore, elevated invertase activity ( Figure 9 E) and higher accumulation of TSS ( Figure 10 C) indicate enhanced sucrose metabolism, thus leading to the formation of hexose sugars during K + supplementation under NaCl stress. Although not much information is available on the role of H 2 S in the modulation of sugar metabolism in plants, Jiang et al [ 53 ] provide a proteomic analysis of H 2 S-responsive proteins, wherein various enzymes of carbohydrate metabolism are modulated in NaCl-stressed cucumber leaves. Modulation of α-amylase and β-amylase activity ( Figure 9 A,B) during NaCl stress and K + and HT treatment indicates the regulation of starch degradation, mediated by endogenous H 2 S signaling.…”
Section: Discussionmentioning
confidence: 99%